Study of sociodemographic factors affecting outcome of babies admitted in neonatal care unit - Kawale, Suchita N.; Shinde, Manjusha A.; Shinde, Prashant S. (International Journal Of Community Medicine And Public Health, 2019)
Background: A country needs sound epidemiological information to prioritize, plan and implement the public health care system effectively. Outcome data from hospitalized patients reflect the causes of major illnesses and care seeking behaviour of the community. Thus, we felt the need to conduct this study at our hospital to assess the socio-demographic factors affecting outcome of babies admitted in neonatal intensive care unit. Methods: The present study was a hospital based observational descriptive study. The study was undertaken in neonatal intensive care unit (NICU) of department of paediatrics of tertiary care centre. The study period was from January 2013 to December 2013 i.e. total period of one year. Results: Among 1050 total neonatal admissions 601 (57.29%), were from rural area and 449 (42.70%) were from urban area. Multinomial regression analysis reveals that socio-demographic factors like age of mother, parental intake of tobacco alcohol in any form, socioeconomic class IV, in born place of delivery, occupation and education of father, low birth weight and male sex of baby affects the outcome of babies. Conclusions: Cure rate in NICU admissions was 69% which may be due to available speciality staff and logistics. Taking this into account, 40 bedded NICU in tertiary care hospital seemed to be essential and sufficient.